Molecular mechanisms of streptococcal disruption of the blood-brain barrier and their pathogenic role in bacterial meningitis - Shi, Yumei; Liang, Tao; Shi, Chao; Yao, Benhai; Xiong, Bo; Zhang, Jun (Frontiers in Immunology, 2026)
Bacterial meningitis represents a devastating inflammatory disease of the central nervous system (CNS), characterized by the invasion of pathogens across the blood-brain barrier (BBB) and subsequent dysregulated immune responses. Key inflammatory mechanisms include pathogen recognition by microglial TLRs and NLRP3, neutrophil infiltration, and cytokine storms such as IL-1β and TNF-α, leading to BBB disruption, cerebral edema, and neuronal injury. Despite antimicrobial therapy, excessive inflammation often results in neurological sequelae. Emerging strategies target immunomodulation through inflammasome inhibitors and BBB preservation using nanoparticle drug delivery to mitigate inflammation-driven CNS damage. This review focuses on the intricate interplay between bacterial virulence factors and neuroinflammatory cascades, with particular emphasis on Streptococcus pneumoniae as a model pathogen. By integrating recent advances in molecular pathogenesis and translational immunology, this review provides a framework for developing precision therapies to mitigate inflammation-mediated CNS damage in bacterial meningitis.